A New Physiological Role for the DNA Molecule as a Protector against Drying Stress in Desiccation-Tolerant Microorganisms - García-Fontana, Cristina; Narváez-Reinaldo, Juan J.; Castillo, Francisco; González-López, Jesús; Luque, Irene; Manzanera, Maximino (Frontiers in Microbiology, 2016)
The DNA molecule is associated with the role of encoding information required to produce RNA which is translated into proteins needed by the cell. This encoding involves information transmission to offspring or to other organisms by horizontal transfer. However, despite the abundance of this molecule in both the cell and the environment, its physiological role seems to be restricted mainly to that of a coding and inheritance molecule. In this paper, we report a new physiological role for the DNA molecule as involved in protection against desiccation, in addition to its well-established main information transfer and other recently reported functions such as bio-film formation in eDNA form. Desiccation-tolerant microorganisms such as Microbacterium sp. 3J1 significantly upregulate genes involved in DNA synthesis to produce DNA as part of their defensive mechanisms to protect protein structures and functions from drying according to RNA-seq analysis. We have observed the intracellular overproduction of DNA in two desiccation-tolerant microorganisms, Microbacterium sp. 3J1 and Arthrobacter siccitolerans 4J27, in response to desiccation signals. In addition, this conclusion can be made from our observations that synthetic DNA protects two proteins from drying and when part of a xeroprotectant preparation, DNA from various organisms including desiccation-sensitive species, does the same. Removal of DNA by nuclease treatment results in absence of this additive protective effect. We validated this role in biochemical and biophysical assays in proteins and occurs in trans even with short, single chains of synthetically produced DNA.